STRUCTURING (DIS)CONNECTIONS: THE INFLUENCE OF TECHNOLOGY ON CONTEMPORARY RELATIONSHIPS (REMUNOM, 2025)
Throughout history, social interactions have evolved significantly. However, with the advancement and growing influence of technology, these interactions have increasingly changed. Interpersonal relationships became more volatile and dynamic, thus causing a profound impact on the way in which the individual constructed their identity and perceived others. Thus, given this scenario, we sought to identify the influence of technology on contemporary interpersonal relationships, changing the understanding of the way it acts on the individual in the social context. To this end, having as a theoretical basis, the research used consisted of an integrative bibliographic review, with the analysis of articles published between 2013 and 2024. The results of this research allowed us to identify an ambiguous scenario, where, on the one hand, technology offers new possibilities of interaction, comfort, quick and convenient connections, on the other hand, it intensifies feelings of helplessness and isolation, aggravated by the superficiality of virtual relationships. We also observe the emergence of phenomena such as “digital narcissism” and “pocket relationships”, which highlight the ephemerality of bonds in the contemporary era. In this way, it can be considered that, although technology has positively transformed the forms of interaction, it also poses challenges to interpersonal relationships, such as the difficulty of establishing deep and authentic connections.